Pencatatan Perkawinan Beda Agama Pasca Dikeluarkannya Surat Edaran Mahkamah Agung RI Nomor 2 Tahun 2023 - Ni Putu Elisa Pebriyanti Putri; I Nyoman Putu Budiartha; I Nyoman Sutama (Fakultas Hukum Universitas Warmadewa, 2024)
Judging from the terms and conditions of its implementation, interfaith marriage combines two different sets of rules based on their respective religious laws. In the case of an application for marriage registration between people of different religions and beliefs, the judge must adhere to the instructions set out in the circular letter that has been issued. Because of the issuance of this circular letter, married couples with different beliefs are not allowed to register their marriages at the Population Office. Researching library sources is one of the methods in conducting legal research. Both statutory methods and conceptual analytical techniques are applied in this research. Samples were obtained, processed, and then examined. After using qualitative material processing procedures, the data was presented using descriptive analysis. Laws governing the union of individuals with different religious beliefs should be included in official policy, as the Human Rights and Marriage Laws have different requirements. Therefore, the government must also quickly harmonize the various regulations related to marriage.